Developing countries' political cycles and the resource curse: Venezuela's case - Alejandro Márquez-Velázquez (Freie Universität Berlin, School of Business & Economics, 2019)
The resource curse literature's main lesson is that developing and natural resource-rich countries should save most of their oil windfalls in foreign currency. Moreover, the political cycle literature's recent contributions predict stronger cycles in these countries. This paper investigates how political cycles might explain low oil windfall savings. Using Venezuela's case, the paper argues that power concentration during periods of oil price explosiveness leads to increased public investment in prestige projects aimed at increasing the incumbent's − or his party's − re-election probabilities. The article backs the argument analyzing the Chavista democratic period of 1999-2016. It also identifies parallels with Venezuela's 1970-1988 period.
urn:nbn:de:kobv:188-refubium-25601-3
Keywords: 330; oil windfalls; political cycles; resource curse; Venezuela